Separation of γ-oryzanol from immature rice seeds by nanofiltration membrane - LI,Dan (2022)
Abstract γ-Oryzanol, which is rich in rice seeds, is natural phytonutrition with many functions such as antioxidant. However, γ-oryzanol has a large loss in the traditional processing, resulting in a huge waste of available resources. In this study, the rice seeds highest content of γ-oryzanol during the development of rice seeds was selected and separated processes by nanofiltration. Several nanofiltration membranes were dramatically applied to condensing phytonutrition under 0.5 Mpa pressure and the flux ranged from 5.8 to 7.7 kg•m-2•h-1. The first processing supplied the separation improving ethanol-extraction system enrichment in γ-oryzanol. In the second, refining ethanol-extraction dramatically reduced the content of free fatty acids, while γ-oryzanol in the retention solution was further significantly increased. Moreover, the isolated γ-oryzanol added in the soybean oil, notably improved antioxidant ability of oil. Our founding can be widely used in the functional food manufacturing and also provides as an available method.